Analisis Kinerja Perusahaan Dengan Metode Break-Even-Sales PT. Lautan Abadi - Arief, Mustika Lukman (Jurnal Ekonomi, 2012)
From financial statement that shows good, accurate, and total count, we can make financial analysis with many view of measurement. Also, we can meke decision about distress or non distress to the financial performance existing. Analysis of financial performance in PT. Lautan Abadi in this research caounted by break-event-sales method which is a method to identify level of sales that shows firm has a break-even condition in financial performance replected by profits or loses would chhanged from full costing method to direct costing method. Then, changing in measurement methode used to count braek-even-sales. Finally, based on financial performance by firm at current period, profits or loses will be predited in the future times.